2014
DOI: 10.1021/nn5011254
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Enhancement Mechanism for the Upconversion Processes in NaYF4:Yb3+,Er3+ Nanoparticles: Maxwell versus Förster

Abstract: Rare-earth activated upconversion materials are receiving renewed attention for their potential applications in bioimaging and solar energy conversion. To enhance the upconversion efficiency, surface plasmon has been employed but the reported enhancements vary widely and the exact enhancement mechanisms are not clearly understood. In this study, we synthesized upconversion nanoparticles (UCNPs) coated with amphiphilic polymer which makes UCNPs water soluble and negatively charged. We then designed and fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
240
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(247 citation statements)
references
References 83 publications
6
240
1
Order By: Relevance
“…Various strategies have been applied to enhance the UC luminescence (UCL), e.g. the iso/hetero-epitaxy growth of protection shells [11,12], spatial design of the doping ions [6,8], and surface plasmon enhancement [13]. In addition, the local structure engineering is also an effective way to modify the UC performance of the materials, since the UC properties are tightly related to the local crystal structures around Ln 3+ ions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been applied to enhance the UC luminescence (UCL), e.g. the iso/hetero-epitaxy growth of protection shells [11,12], spatial design of the doping ions [6,8], and surface plasmon enhancement [13]. In addition, the local structure engineering is also an effective way to modify the UC performance of the materials, since the UC properties are tightly related to the local crystal structures around Ln 3+ ions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…20−25 Electric field localization enhances absorption, 26−28 improves the spontaneous emission rate, 29 and the energy transfer rate. 30 Recent studies have shown that coupling UC materials with metal nanostructures such as array of metallic nanostructures, 31,32 metallic codoped nanocrystals, 23 and metal nanohole array 33 enables a straightforward amelioration in UC efficiency. Despite the theoretical and experimental expectations of these approaches, they have achieved only mild emission enhancement for device application, and their fabrication in scalable areas is far from easy and is expensive.…”
mentioning
confidence: 99%
“…From the experimentally observed enhancements, we concluded enhancement factors of 3.1 and 1.3 for absorption and energy transfer, respectively. [5] This study clearly elucidates the plasmon enhancement mechanism, allowing the fair comparison between various plasmonic UCNP systems and also the rational design of optimal plasmonic structures. …”
Section: Plasmon Enhanced Frequency Upconversionmentioning
confidence: 81%